TINJAUAN PROGRAM VISIT MAKASSAR YEAR 2011 DI KOTA MAKASSAR - Abdul Khalik (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aims To Visit Makassar Reviewing Program Year 2011 to the level of Domestic Tourist Arrivals and Manca-State in Makassar and To know the Program Year 2011 to Visit Makassar Room Occupancy Hotels in Makassar. The results showed that the application of Makassar Visit Program Year 2011 to increase the level of domestic tourist visits (domestic) and foreign tourists. Visit Makassar Year Program to increase hotel occupancy rates as Makassar and may increase the contribution program to Visit Makassar Year 2011 Revenue Makassar is quite large, and the level of investment in the tourism sector, particularly in the city of Makassar. Visit Makassar Year Program to encourage the growth of the hospitality industry dibdang, Nightlife, Restaurants and Eating for 7 (seven) years have increased from year to year.